Rowley Jefferson's Awesome Spooky Stories - Kinney, Jeff; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; Kinney, Jeff.; et al. (New York : Amulet Books, 2021)
"Grab a flashlight, crawl under the covers, and dive into the twisted, unexpectedly hilarious world of Rowley Jefferson's imagination. You'll meet zombies, vampires, ghosts, and much more in these comically terrifying tales. Rowley's spooky stories might leave you laughing, but beware--you could end up sleeping with the lights on"--
Keywords: Friendship in children -- Juvenile fiction; Adventure stories; Paranormal fiction; Ghost stories; Friendship -- Fiction; Adventure and adventurers -- Fiction; Supernatural -- Fiction; Ghosts -- Fiction; Humorous Stories; Short stories